Multinationals and transition : - Manea, Julia (Palgrave Macmillan, 2004)
This book refocuses thinking on how multinational enterprises (MNEs) can achieve a sustained contribution to European transition economies as these countries move from the processes of transformation into pursuit of more sustained development. The authors apply key aspects of recent work on the strategic aims and nature of the contemporary MNE to the transition economy context, and find that the generation and application of technology has particular relevance to the success of MNEs in Central and Eastern Europe. The book is based on the results of two new wide-ranging surveys and includes a thorough review of current literature.